2020
DOI: 10.3390/en13051241
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Depolymerization of Biorefinery Lignin-Rich Streams: Influence of Reaction Conditions and Catalytic Additives on the Organic Monomers Yields in Biocrude and Aqueous Phase

Abstract: Hydrothermal depolymerization of lignin-rich streams (LRS) from lignocellulosic ethanol was successfully carried out in a lab-scale batch reactors unit. A partial depolymerization into oligomers and monomers was achieved using subcritical water as reaction medium. The influence of temperature (300–350–370 °C) and time (5–10 minutes) was investigated to identify the optimal condition on the monomers yields in the lighter biocrude (BC1) and aqueous phase (AP) fractions, focusing on specific phenolic classes as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The lignin-rich stream was produced in an industrial-scale lignocellulosic ethanol demo plant located in Northern Italy [18], where poplar was used as raw material. A different batch of the same material was converted via hydrothermal liquefaction and its characterization is reported in Dell'Orco et al [15]. The properties of the sample used in the present study are reported in the Results Section and are compared with those of a sulfur-free lignin from soda pulping [14].…”
Section: Feedstockmentioning
confidence: 99%
See 2 more Smart Citations
“…The lignin-rich stream was produced in an industrial-scale lignocellulosic ethanol demo plant located in Northern Italy [18], where poplar was used as raw material. A different batch of the same material was converted via hydrothermal liquefaction and its characterization is reported in Dell'Orco et al [15]. The properties of the sample used in the present study are reported in the Results Section and are compared with those of a sulfur-free lignin from soda pulping [14].…”
Section: Feedstockmentioning
confidence: 99%
“…Fructose can also lead to the formation of glyceraldehyde, which can consequently produce glycolic acid or pyruvaldehyde, which in turn forms acetic acid. Among the quantified compounds, lactic acid was the most abundant, reaching nearly 5 g L −1 at 270 • C, 2 h. Glycerol, lactic and acetic acid were also found in the raw feedstock [15], and derive from the bacterial contamination of the poplar fermentation process from which the lignin-rich stream was obtained.…”
Section: Htc Aqueous Phase Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal depolymerization of lignin-rich streams (LRS) from lignocellulosic ethanol was successfully carried out in a lab-scale batch reactors unit, varying parameters such as temperature, time and introducing KOH and supercritical carbon dioxide (sCO2) as catalysts for process optimization [13]. A partial depolymerization was achieved using subcritical water as a reaction medium.…”
Section: Hydrothermal Depolymerization Of Biorefinery Lignin-rich Streams: Influence Of Reaction Conditions and Catalytic Additives On Thmentioning
confidence: 99%
“…Dell'Orco et al [2] examined Lignin-Rich Stream (LRS) feedstock from lignocellulosic ethanol for hydrothermal liquefaction. Micro-batch reactors were used to carry out the experimental investigation, focusing the analysis mostly on temperature and residence times, ranging from 300 • C to 370 • C and 5 to 10 min, respectively.…”
mentioning
confidence: 99%